2017
DOI: 10.4103/0259-1162.200238
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation of nonparalyzed patients under anesthesia with laryngeal mask airway, comparison of three modes of ventilation: Volume controlled ventilation, pressure controlled ventilation, and pressure controlled ventilation-volume guarantee

Abstract: Background:Pressure controlled ventilation (PCV) is the preferable mode of ventilation of nonparalyzed patients undergoing anesthesia with laryngeal mask airway (LMA) as compared to volume controlled ventilation (VCV) and spontaneously breathing patient. In this study, we compared the PC–volume guarantee (PC-VG) mode of ventilation with VCV and PCV modes.Materials and Methods:A total of 30 patients, American Society of Anesthesiologists (ASA) physical status Classes I and II, scheduled for elective surgery und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Furthermore, the efficacy of the use of DCV in supraglottic airway devices has not been extensively studied. Ghabach et al, in an observational study, have reported lower PAWP with PCV and PCV-VG than with VCV in patients ventilated using LMA Classic, along with no airway leaks in any ventilation mode in any of the patients [ 13 ]. These reports suggest that PCV and DCV are preferable to VCV for regulating PAWP in patients ventilated using supraglottic airway devices [ 4 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the efficacy of the use of DCV in supraglottic airway devices has not been extensively studied. Ghabach et al, in an observational study, have reported lower PAWP with PCV and PCV-VG than with VCV in patients ventilated using LMA Classic, along with no airway leaks in any ventilation mode in any of the patients [ 13 ]. These reports suggest that PCV and DCV are preferable to VCV for regulating PAWP in patients ventilated using supraglottic airway devices [ 4 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…P < 0.01 was considered statistically significant. The sample size was based on previous studies [ 15 ], in which the difference in mean PIP between both modes of ventilation was 3 cm H 2 O, with a standard deviation of 3 cm H 2 O. Using α of .01 and desired power of 90%, 64 participants were determined to be needed to demonstrate a statistically significant difference.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Some researchers have compared the VCV and PCV-VG ventilation among the adult group. 4 , 5 However, the effect of respiratory dynamics in pediatric patients undergoing VCV and PCV-VG ventilation with laryngeal mask airway is still unclear.…”
Section: Introductionmentioning
confidence: 99%